Implementasi Struktur Data Antrian Queue dalam Sistem Penjadwalan Proses pada Sistem Operasi - Azura Trijayanti; Intan Aulia; Nazwa Khairunisa; Farhan Asyrof Hamadi Purba; Indra Gunawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Data structures are a fundamental conceptin computer science used to store, organize, and mange data within a program or computer system. The selection of the appropriate data structure plays a crucial role in optimizing both time and space efficiency in data processing. Generally, data structures are classified into two main categories: linear and non-linear structures. Linear data structures include arrays, linked lists, stacks, and qeueues, where elements are arranged in a sequential order. Non-linear data structures, on the other hand, include trees and graphs, which organize element in more complex relationship. Each type of data structure has specific characteritics and operations that can impact the performance of aplications, such as searching, insertion, and deletion of data. The choice of the right data structure is essential in algortihm design as it can significantly enhance the efficienty and effectiveness of a system or application.